THE EFFECT OF LEVERAGE, LIQUIDITY, INDEPENDENT COMMISSIONERS, AND FIRM SIZE ON FIRM VALUE: A STUDY OF IPO-LISTED HEALTHCARE COMPANIES IN INDONESIA FROM 2018 TO 2023 - Muhammad Rizqi Syahri Romdhon; Silviana (UPT Publikasi Ilmiah UNISBA, 2025)
The purpose of this study is to investigate how company size, independent commissioners, leverage, and liquidity affect firm value in the healthcare industry listed on the Indonesia Stock Exchange (IDX) between 2018 and 2023. Panel data regression using the Fixed Effect Model (FEM) approach is the analytical technique employed. With a total of 90 observations, the study sample comprises 15 organizations chosen through the use of purposive selection. Leverage has no discernible impact on business value, according to the findings. On the other hand, firm size, independent commissioners, and liquidity all significantly affect firm value. According to these results, investor views of business value are significantly influenced by internal characteristics including liquidity and corporate governance procedures, especially the existence of independent commissioners. The drivers of business value, particularly in the healthcare industry, are better understood by investors, corporate management, and scholars thanks to this study.